Kontrol Negara Terhadap Pegawai Negeri Sipil (Studi Atas Peraturan Pemerintah No.10 Tahun 1983 Jo No.45 Tahun 1990 Tentang Perkawinan) - Siska Putriana; Ujang Wardi; Elfia Elfia (Indonesian Center for Religion and Society Studies (InTReSt), 2021)
This study explains how the state controls the Civil Servants (PNS). The research uses the Library Research method with the type of normative legal research through a statute approach. The method used is to analyze the laws and regulations and the Presidential Decree (PP). There are three forms of regulatory data analyzed, first, primary data consisting of the 1945 Constitution, Law No. 1 of 1974 concerning Marriage, Law No. 8 of 1974 concerning Basic Personnel, Law No. 5 of 2014 concerning ASN, Law No. 17 of 2014 concerning the MPR, DPR, DPD, DPRD PP No. 10 of 1983 in conjunction with PP No. 45 of 1990 concerning Marriage and Divorce Permits for Civil Servants. Second Secondary which consists of legal writings, expert opinion focused on family law. The second secondary data consists of legal writings, expert opinions focused on family law. Third, tertiary data, information obtained from primary and secondary legal materials; legal dictionaries, world encyclopedias, and also the Big Indonesian Dictionary in order to provide an understanding of the terms used by the law. The approach in this study uses the theory of the state, law and function in looking at the position of civil servants and the involvement of the state in regulating marriage for civil servants. The results of this study indicate that there are two forms of state interest in regulating the behavior of civil servants; 1) political loyalty, 2) sexuality restrictions on civil servants (PNS).